2016
DOI: 10.12924/cis2016.04010028
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating the Glocal Garden

Abstract: This paper addresses the question under which conditions small-scale urban agriculture (UA) initiatives can accelerate a sustainability transition of the global food system. It develops the notion of a glocal garden, a large number of likeminded local initiatives with a global impact and forms of worldwide collaboration. Taking a transition perspective, the glocal garden, producing vegetables and fruits, is a niche that has to overcome barriers to compete with the dominant food regime. Since a sustainability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Hischemöller [62] outlined that gardening in public spaces may not be appreciated by urban residents who associate these practices with dirtiness and hard work, want to spend their time with friends and family doing activities other than gardening, or who do not care so much about new social relationships as they lack the time to maintain their current friendships. Furthermore, Specht et al [63] identified that urban gardens are sometimes perceived as a competitive use of urban land that can lead to conflicts.…”
Section: Benefits and Challenges Of Urban Horticulture On Vacant Landsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hischemöller [62] outlined that gardening in public spaces may not be appreciated by urban residents who associate these practices with dirtiness and hard work, want to spend their time with friends and family doing activities other than gardening, or who do not care so much about new social relationships as they lack the time to maintain their current friendships. Furthermore, Specht et al [63] identified that urban gardens are sometimes perceived as a competitive use of urban land that can lead to conflicts.…”
Section: Benefits and Challenges Of Urban Horticulture On Vacant Landsmentioning
confidence: 99%
“…Since urban agriculture is strongly linked to bottom-up processes rather than top-down urban planning schemes [106], local municipalities need to establish participatory and multi-stakeholder dialogues to integrate bottom-up perspectives and practices in urban planning, particularly regarding urban regeneration actions and plans. In particular, such action might avoid the social unacceptance of top-down urban gardens in areas where citizens are not interested or have other claims [62] and thus reject the garden, as happened to the case Orti della Fornace or in the start-up phase of GreenHousing rooftop garden.…”
Section: Policy-making Recommendationsmentioning
confidence: 99%